Dalle tradizioni costituzionali comuni all’identità costituzionale il passo è breve? Riflessioni introduttive (Stato, Chiese e pluralismo confessionale, 2019)
SOMMARIO: 1. L’identità costituzionale: un crocevia nel rapporto fra ordinamenti - 2. Un’istantanea del dibattito - 3. Visto da Lussemburgo: la prospettiva della Corte di giustizia.From common constitutional traditions to constitutional identity: is it a short road? A critical introductionABSTRACT: Constitutional identity has lately emerged as the most relevant argument underlying the dialogue between the national constitutional courts and the European Court of Justice nowadays. As a matter of fact, this new identitarian seam of the constitutional discourse represents the real battlefield between the national constitutional dimension and the European one. In order to analyse the main features of the EU legal landscape upon which this discussion takes place, this essay investigates the gradual development of the use of the common constitutional traditions as well as the progressive emergence of the concept of constitutional identity as a fundamental element of the whole EU integration process up to including in the Lisbon Treaty a specific provision on this matter, i.e. Art. 4, 2 TEU.